Student leaders: How do they perceive community service activities? / Musramaini Mustapha ...[et al.] - Mustapha, Musramaini; Baharum, Norzie Diana; Mohamad, Siti Aishah; Azer, Ilyani; A Rashid, Ruzaidah (2014)
Most of higher learning institutions conduct community service activities involving both the students and staff. In some foreign universities, community service is even tailored as grade-earning courses that benefit the students academically and socially. With the numerous benefits gained from the activity, this paper explored the perceptions and attitudes of the student leaders on community service activity. This study was conducted in two universities in Pahang, Universiti Teknologi Mara Pahang (UiTM Pahang) and Universiti Malaysia Pahang (UMP). It applied The Community Service - Learning Attitudes and Perception Scale (CSLAPS). The findings showed that the student leaders from UiTM Pahang were more socially-driven in contrast to the UMP SRC who were mostly academically driven while engaging themselves with community based programmes. They also showed an interest in joining the activities in the future and most of the student leaders from these two institutions could see the importance of such activities. This research information could be used by the learning institutions to engage their student leaders in an academic based community service as a way of learning and contributing back to the society and to create versatility among the future leaders.